The Utilization of Fiddle-Leaf Fig Waste Into Food Preservative - Astuti, Erna; Mufrodi, Zahrul (Universitas Negeri Semarang, 2019)
Fiddle-leaf Fig is a tree that is widely used as a protective or plants or shade. This plant is usually found on the side of the road, in the office area and as houseplants.Ã‚Â The presence of fiddle-leaf fig leaves that fall from the tree will be a waste for the environment. This study proposes utilization of fiddle-leaf fig waste by pyrolysis method using pyrolysis triple condenser. Thermal analysis was done before experiments using a thermo gravimetric analyzer in the range of temperature of room temperature until 1000 Ã‚ÂºC. Process was carried out at heating temperature of 350Ã‚ÂºC, 375Ã‚ÂºC, 400Ã‚ÂºC, 425Ã‚ÂºC, 450Ã‚ÂºC, 475Ã‚ÂºC and 500Ã‚ÂºC. The product of pyrolysis were obtained from liquid coming out from the residue container, the first and second condenser, and the smoke is coming out from the third condenser. The smokes were absorbed with water. Further, all of the liquid were analyzed by gas chromatography mass spectrometry (GCMS). The analysis results show that the main components of pyrolysis liquid products are carboxylic acids, ketones, alcohols, and alkanes. There is gasoline and kerosene in the liquid, so it has the potential to become bio-oil. The largest potential of fiddle-leaf fig waste is as raw material for food preservative because it contains many carboxylic acid compounds.